Trapping of H II regions in Population III star formation - Jaura, Ondrej; Glover, Simon; Wollenberg, Katharina M. J.; Klessen, Ralf S.; Geen, Samuel Thomas; Haemmerlé, Lionel (Monthly notices of the Royal Astronomical Society, 2022)
Radiative feedback from massive Population III (Pop III) stars in the form of ionizing and photodissociating photons is widely believed to play a central role in shutting off accretion on to these stars. Understanding whether and how this occurs is vital for predicting the final masses reached by these stars and the form of the Pop III stellar initial mass function. To help us better understand the impact of UV radiation from massive Pop III stars on the gas surrounding them, we carry out high-resolution simulations of the formation and early evolution of these stars, using the arepo moving-mesh code coupled with the innovative radiative transfer module sprai. Contrary to most previous results, we find that the ionizing radiation from these stars is trapped in the dense accretion disc surrounding them. Consequently, the inclusion of radiative feedback has no significant impact on either the number or the total mass of protostars formed during the 20 kyr period that we simulate. We show that the reason that we obtain qualitatively different results from previous studies of Pop III stellar feedback lies in how the radiation is injected into the simulation. H ii region trapping only occurs if the photons are injected on scales smaller than the local scale height of the accretion disc, a criterion not fulfilled in previous 3D simulations of this process. Finally, we speculate as to whether outflows driven by the magnetic field or by Lyman-α radiation pressure may be able to clear enough gas away from the star to allow the H ii region to escape from the disc.
Gesehen am 21.04.2022